Types and Abundance of Peripyhton in The Plastic Substrate in The Sail River, PekanbaruCity, Riau Province - Syada Nopriadi Akbar; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTPeriphyton is a sessile microscopic organism that attach on certain substrate. Research aims to determine the type and abundance of periphyton on plastic substrate has been carried out in April-May 2018 in the Sail River. There were three sampling stations, namely S1 (in the upstream), S2 (in the middle) and S3 (in the downstream). Samplings were conducted once/week for a 3 weeks period. The periphyton samples are brushed from the plastic substrates (8x6) cm2. The number of substrates in S1, S2 and S3 were 5, 4, and 3 pieces respectively. Water quality parameter measured were water current, temperature, transparency, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate. Results shown that there were 33 types of periphyton present and they were belonged 4 classes, namely Bacillariophyceae (13 species), Cyanophyceae (10species), Chlorophyceae (9 species) andEuglenaphyceae(1species). The abundance of periphyton in the plastic substrate in the S1 was 15,658 cells/cm2, in S2 was 22,095 cells/cm2and in S3 there was 30,799 cells/cm2.The water quality parameters were as follows: water current 0.07-0.69 m/s. transparency 6.03-7.67 cm, temperature 29-300C, dissolved oxygen 4.8-5.7 mg/L, free carbon dioxide13.6-14.6 mg/L, nitrate 0.29-0.38 mg/L, phosphate 0.34-0.54 mg/L. Based on the type of peryphyton present, indicate the trophic state of the Sail River as eutrophic. Keywords: Lotic, sessileorganism, water quality, trophic state